2003
DOI: 10.1097/00005176-200309000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Can Pre-Neoplastic Lesions be Detected in Gastric Biopsies of Children with Helicobacter pylori Infection?

Abstract: We describe intestinal metaplasia associated with H. pylori infection in children. Since atrophy usually precedes intestinal metaplasia in adults, we suggest that atrophy exists in children. High numbers of B lymphocytes and apoptosis in the surface epithelium are seen in patients with H. pylori infection and may be related to the development of atrophy and intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 18 publications
2
58
1
Order By: Relevance
“…Similar changes have been observed in previous studies that evaluated the apoptosis of gastric mucosa inflammatory cells showing an increased apoptosis of CD4 + T-cell subset using immunohistochemistry methods [Guarner et al, 2003, Kotłowska-Kmieć et al, 2009.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar changes have been observed in previous studies that evaluated the apoptosis of gastric mucosa inflammatory cells showing an increased apoptosis of CD4 + T-cell subset using immunohistochemistry methods [Guarner et al, 2003, Kotłowska-Kmieć et al, 2009.…”
Section: Discussionsupporting
confidence: 86%
“…The majority of the infected children do not suffer from acute inflammatory complications and a few develop severe diseases such as peptic ulcer (Queiroz et al, 1991), mucosal atrophy, gastric carcinoma or MALT lymphoma (Guarner et al, 2003). The cellular basis for the mild gastric inflammatory changes in children with H. pylori infection is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial overgrowth may be more frequent. In contrast to adults, preneoplastic lesions are exceptional (193), even in high risk areas (465). The infection is seldomly found in infants and young children, which limits the possibilities of test comparisons on large series.…”
Section: Application In Different Clinical Settingsmentioning
confidence: 99%
“…Guarner et al have observed gastric atrophy in 8, intestinal metaplasia in 2 and both in 2 patients out of 19 children. 15 All children were infected with H.pylori and all patients with intestinal metaplasia were older than 9 years. Atrophy was seen in 10 patients, all in the antrum, and metaplasia in 4 patients, 3 in the antrum and 1 in the corpus.…”
Section: Discussionmentioning
confidence: 99%